Iraq Crude Oil Exports– April, May, June 2019 - SOMO, Ministry of Oil - Oil Marketing Company (Journal of Petroleum Research and Studies, 2021)
Table 1. Iraq Crude Oil Exports – April 2019 Table 2. Iraq Crude Oil Exports – May 2019 Table 3. Iraq Crude Oil Exports – June 2019